2022
DOI: 10.2993/0278-0771-42.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Knowledge of Agave Landraces, Uses, and Management in Nanacamilpa, Tlaxcala

Abstract: Pulque is a product made from the fermentation of the sap (aguamiel) of certain agaves and its consumption has been recorded since pre-Hispanic times. The effort to recognize the landraces of the Agave genus used to produce pulque and the study of its traditional knowledge remain limited. Studies regarding this topic have centered on farmers (experts) with the biggest production capacity. This work analyzes in different ways the knowledge that experts and non-experts (general population) have regarding the usa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…salmiana for 10 localities in 9 municipalities of Tlaxcala. Finally, Trejo et al (2022) reported, for the central zone of Nanacamilpa, Tlaxcala, A. americana "Cenizo", A. mapisaga var. mapisaga "Palmilla", A. salmiana subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…salmiana for 10 localities in 9 municipalities of Tlaxcala. Finally, Trejo et al (2022) reported, for the central zone of Nanacamilpa, Tlaxcala, A. americana "Cenizo", A. mapisaga var. mapisaga "Palmilla", A. salmiana subsp.…”
Section: Discussionmentioning
confidence: 99%
“…According to these reports, "Manso" is preferred because of its size, the flexibility of its leaves that facilitate handling, and, most of all, https://doi. org/10.22201/ib.20078706e.2023.94.4979 the high quality of its sweeter sap of 9-15 °Brix (Mora-López et al, 2011;Ramírez-Manzano et al, 2020;Trejo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De los agaves pulqueros, particularmente, se obtienen recursos comestibles como: chinicuiles, gusano blanco de maguey y hongo de maguey. Se han agrupado cerca de 100 usos específicos (Colunga-GarcíaMarín et al 2017; Trejo et al 2022), y para cada parte de la planta en las distintas fases de su crecimiento provee de diversos recursos (Bucio Peña et al 2023).…”
Section: Introductionunclassified